SEVERITY OF CLINICAL SYMPTOMS IN PATIENTS WITH NEGATIVE SYMPTOMS IN SCHIZOPHRENIA - Кушнір, Юрій (SWorldJournal, 2023)
252 patients with negative symptoms (NS) of schizophrenia and 79 patients with positive symptoms of schizophrenia were examined. A comprehensive approach was used, consisting of a combination of clinical and anamnestic, clinical and psychopathological an